Measuring The Knowledge Level of Healthcare Personnel on Information Security (Third Sector Social Economic Review, 2026)
Information security has become a global priority and an increasingly comprehensive field of concern. Despite its critical importance for patient safety, it is not accorded sufficient attention in practice. Although significant progress has been made in establishing legal and regulatory frameworks to ensure information security, the development of an effective and holistic security ecosystem necessitates multidimensional structural transformations encompassing human factors, technological systems, and organizational processes. Healthcare institutions constitute attractive targets for cybercrime due to the richness and value of the data they generate and store. Cybersecurity breaches in the healthcare sector include unauthorized access to patient information and ransomware attacks targeting healthcare organizations, thereby threatening both data confidentiality and service continuity. Such breaches may undermine patient trust, disrupt the functioning of healthcare systems, and ultimately pose risks to human life. The primary aim of this study is to identify structural and practice-based deficiencies in the use of information management systems based on healthcare personnel’s perceptions and evaluations regarding information security. A convenience sampling method was employed, and data were collected through a questionnaire. Healthcare personnel were categorized into administrative and clinical units according to their departments, and differences in perceptions between these groups were examined. The findings indicate that 25% of participants do not demonstrate an adequate level of awareness and diligence regarding information security. Furthermore, training programs related to information management systems were found to be insufficient in terms of both duration and content. Ensuring the security of data generated and stored within healthcare institutions, as well as preventing potential data loss, requires particularly clinical staff to undergo structured training programs of adequate duration and scope.
Keywords: Information Security; Hospital Information Management System; Healthcare Personnel